Calcific tendinitis of the shoulder in the Korean population: demographics and its relation with coexisting rotator cuff tear - Yon-Sik Yoo; Jin-Young Park; Myung-sun Kim; Nam-Su Cho; Yong-Beom Lee; Seung-Hyun Cho; Kyoung Jin Park; Chul-Hyun Cho; Bong Gun Lee; Dong Joo Shin; Han-Hoon Kim; Tae Kang Lim (Clinics in Shoulder and Elbow, 2021)
Background To evaluate the demographics, clinical and radiographic features of calcific tendinitis of the shoulder in the Korean population, specifically focusing on the incidence of coexisting rotator cuff tear. Methods Between October 2014 and January 2015, we performed a prospective multicenter study with 506 patients from 11 training hospitals in Korea. We collected data of demographics and radiographic analysis based on simple radiographs, clinical assessments based on visual analog scale (VAS) and the American Shoulder Elbow Surgeons (ASES) score, and treatment modalities that are used currently. We also evaluated coexisting rotator cuff tear by ultrasonography (US) or magnetic resonance imaging (MRI) images. Results There were 402 female patients (79%) with mean age of 55 years (range, 31–87 years). Mean duration of symptoms was 16 months. Mean size of calcific materials was 11.4 mm (range, 0–35 mm). Mean value of VAS and ASES scores were 6.5 (range, 1–10) and 47 (range, 8–95), respectively. Of 383 patients (76%), 59 (15%) had rotator cuff tear including 15 full-thickness tears on US or MRI. Patients with rotator cuff tears were significantly associated with older age, recurrent symptoms, menstrual disorders in females, and having undergone calcification removal surgery and rotator cuff repair (all p<0.05). Conclusions This study reported demographic, radiographic, and clinical features of calcific tendinitis of the shoulder in Korean population, which were not different from those of Western population. Coexisting rotator cuff tear was found with 15% incidence in this large series, suggesting that further radiographic study to evaluate rotator cuff tear might be needed in some calcific tendinitis patients of older age and presenting with recurrent symptoms.